MicroRNA miR-150 is involved in Vα14 iNKT cell development and function - Zheng, Quanhui (J Immunol, 2012)
CD1d-restricted Vα14 invariant natural killer T (iNKT) cells play an important role in the regulation of diverse immune responses. MicroRNA mediated RNA interference is emerging as a crucial regulatory mechanism in the control of iNKT cells differentiation and function. Yet, roles of specific microRNAs in the development and function of iNKT cells remain to be further addressed. Here, we identified the gradually increased expression of miR-150 during the maturation of iNKT cells in thymus. Using miR-150 knockout (KO) mice, we found that miR-150 deletion resulted in an interruption of iNKT cell final maturation in both thymus and periphery. Upon activation, iNKT cells from miR-150KO mice showed significantly increased IFN-γ production compared to wild type (WT) iNKT cells. Bone marrow transferring experiments demonstrated the cell-intrinsic characteristics of iNKT cell maturation and functional defects in mice lacking miR-150. Furthermore, miR-150 target c-Myb was significantly up-regulated in miR-150KO iNKT cells, which potentially contribute to iNKT cell defects in miR-150KO mice. Our data define a specific role of miR-150 in the development and function of iNKT cells.